2015
DOI: 10.1016/j.agee.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Ants in citrus: impact on the abundance, species richness, diversity and community structure of predators and parasitoids

Abstract: Although ants act as plant biotic defences, in agricultural ecosystems they are often associated with outbreaks of honeydew-producing pests mainly due to the protection they offer to the plant feeders in exchange for honeydew. In such an interaction ants may alter the abundance, diversity and community structure of predators and parasitoids. In the present study, we conducted ant-exclusion experiments in three commercial citrus orchards, each one dominated by one ant species (Pheidole pallidula, Lasius grandis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 69 publications
1
26
0
3
Order By: Relevance
“…In this case, P. gallicus was found to prey on both psyllids and aphids but predation was greatly reduced in the presence of ants. These observations are in agreement with the ant– P. gallicus negative interaction registered in the field, but in contrast with the positive correlation reported by other authors . Evidence of ant avoidance behaviour, such as spatial segregation, was found in spiders from the analysis of field data.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this case, P. gallicus was found to prey on both psyllids and aphids but predation was greatly reduced in the presence of ants. These observations are in agreement with the ant– P. gallicus negative interaction registered in the field, but in contrast with the positive correlation reported by other authors . Evidence of ant avoidance behaviour, such as spatial segregation, was found in spiders from the analysis of field data.…”
Section: Discussionmentioning
confidence: 85%
“…These observations are in agreement with the ant-P. gallicus negative interaction registered in the field, but in contrast with the positive correlation reported by other authors. 69,70 Evidence of ant avoidance behaviour, such as spatial segregation, was found in spiders from the analysis of field data. Other authors have also reported spatial segregation of ants and spiders.…”
Section: Discussionmentioning
confidence: 99%
“…Hemipteran honeydew is an important nutrient source for Argentine ants, and the presence of Argentine ants harvesting honeydew protects hemipteran pests from natural enemies . Thus, effective Argentine ant management in agricultural environments is necessary to maximize the effectiveness of natural enemies attacking plant pests …”
Section: Introductionmentioning
confidence: 99%
“…According to the results of this Other study showed that Dermaptera of genus Dorus are efficient herbivorous predators in corn monoculture (see Cruz 1991). Additionally, Buschman et al (1977) Some studies have shown that the result of ant-plant interaction is dependent of the species of predatory ants involved interaction (Byk & Del-Claro, 2010;Calabuig et al, 2015) and of the strategies of herbivorous against predation (Bächtold & Alves-Silva, 2013;Carita et al, 2006;Styrsky & Eubanks, 2010). Nevertheless, little is known about the behavior between pairs (predator-prey) determining plant protection.…”
Section: Discussionmentioning
confidence: 99%
“…Elements such as ant species features (Byk & Del-Claro, 2010;Calabuig et al, 2015), their density (De la Mora et al, 2015) and also herbivorous defense strategy against predation (Bächtold & Alves-Silva, 2013) however, some species may be more influenced than others.…”
Section: Introductionmentioning
confidence: 99%